Analisis Kepemimpinan Andi Amran Sulaiman Dalam Pengambilan Keputusan Kebijakan Swasembada Pangan Di Indonesia - Zahra Lathifah Marfi; Nabila Herman; Sypa Zahwatul Aini; Muhammad Hafiizh Syam; Yulia Hanoselina (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Food security has become a strategic issue in Indonesia amid challenges posed by climate change, population growth, and global food supply instability. This study aims to analyze Andi Amran Sulaiman's leadership in food self-sufficiency policy decision-making, the decision-making process employed, and its impact on national food self-sufficiency. This study applies transformational leadership theory to examine how a vision for change and innovation was built within this leadership. A qualitative approach was employed using the Systematic Literature Review (SLR) method with a thematic-narrative analysis technique. Data were collected through document analysis of scientific articles obtained from the Scopus, SINTA, and Google Scholar databases. The findings indicate that Andi Amran Sulaiman's leadership reflects transformational characteristics supported by data-driven decision-making, contributing to agricultural modernization, increased productivity, and strengthened national food security, despite facing several implementation challenges.